Improving Financial Literacy of Lampung Millennial Generation MSME Actors through Cash Management Training and Assistance - Vitria Susanti; A Zuliansyah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service initiative aims to enhance the financial literacy of millennial MSME actors in Lampung through targeted cash management training and assistance. The primary objective is to equip participants with essential financial skills, enabling them to make informed decisions and improve their business sustainability. Utilizing the Participatory Action Research (PAR) method, the program engages participants in a collaborative learning process, fostering ownership and relevance in the training content. Results indicate a significant improvement in participants' understanding of cash flow management, budgeting, and financial planning. Pre- and post-training assessments revealed a marked increase in financial literacy scores, demonstrating the effectiveness of the training. Additionally, participants reported increased confidence in managing their finances and making strategic business decisions. However, the initiative faced practical limitations, including varying levels of initial financial knowledge among participants and limited access to financial resources. Theoretical limitations include the challenge of measuring long-term impacts on business performance and financial stability. Despite these challenges, the program highlights the importance of tailored financial education for millennial MSME actors, contributing to their empowerment and the overall economic development of the Lampung region. Future efforts should focus on sustaining financial literacy initiatives and addressing resource accessibility to maximize impact.